FIQH AL-BI’AH: PRINSIP INTERAKSI MANUSIA DENGAN ALAM PERSEKITARAN - Mahad Musa, Zahari (Jurnal Syariah, 2010)
Pollution should be dealt with seriously by all relevant parties. The media discovered a number of environmental offenses including toxic dumping and illegal logging. The need to understand fiqh al-bi’ah has been there in Islamic law. There is a need to address the failure of understanding the importance of this matter. Placing fiqh al-bi’ah in its proper place ensures the sustainability of the environment thus encourages the community growth in cleaner environment. This article aims to discuss the Syari’ah principles with regards to human and environment relationship based on Islamic legal texts of al-Quran and al-Sunnah. The surrounding discussion in this paper focuses the role of human, given the faculty of mind, as administrators of the earth towards it betterment and not the vice versa. The study of fiqh al-bi’ah unveils the beauty of Islam in addressing environmental concerns and matters related to it.